Control over structure‐specific flexibility improves anatomical accuracy for point‐based deformable registration in bladder cancer radiotherapy. Issue 2 (7th January 2013) - Wognum, S.; Bondar, L.; Zolnay, A. G.; Chai, X.; Hulshof, M. C. C. M.; Hoogeman, M. S.; Bel, A.
Abstract : Purpose: : Future developments in image guided adaptive radiotherapy (IGART) for bladder cancer require accurate deformable image registration techniques for the precise assessment of tumor and bladder motion and deformation that occur as a result of large bladder volume changes during the course of radiotherapy treatment. The aim was to employ an extended version of a point‐based deformable registration algorithm that allows control over tissue‐specific flexibility in combination with the authors' unique patient dataset, in order to overcome two major challenges of bladder cancer registration, i.e., the difficulty in accounting for the difference in flexibility between the bladder wall and tumor and the lack of visible anatomical landmarks for validation. Methods: : The registration algorithm used in the current study is an extension of the symmetric‐thin plate splines‐robust point matching (S‐TPS‐RPM) algorithm, a symmetric feature‐based registration method. The S‐TPS‐RPM algorithm has been previously extended to allow control over the degree of flexibility of different structures via a weight parameter. The extended weighted S‐TPS‐RPM algorithm was tested and validated on CT data (planning‐ and four to five repeat‐CTs) of five urinary bladder cancer patients who received lipiodol injections before radiotherapy. The performance of the weighted S‐TPS‐RPM method, applied to bladder and tumor structures simultaneously, was compared with a previous version of the S‐TPS‐RPM algorithm applied to bladder wall structure alone and with a simultaneous nonweighted S‐TPS‐RPM registration of the bladder and tumor structures. Performance was assessed in terms of anatomical and geometric accuracy. The anatomical accuracy was calculated as the residual distance error (RDE) of the lipiodol markers and the geometric accuracy was determined by the surface distance, surface coverage, and inverse consistency errors. Optimal parameter values for the flexibility and bladder weight parameters were determined for the weighted S‐TPS‐RPM. Results: : The weighted S‐TPS‐RPM registration algorithm with optimal parameters significantly improved the anatomical accuracy as compared to S‐TPS‐RPM registration of the bladder alone and reduced the range of the anatomical errors by half as compared with the simultaneous nonweighted S‐TPS‐RPM registration of the bladder and tumor structures. The weighted algorithm reduced the RDE range of lipiodol markers from 0.9–14 mm after rigid bone match to 0.9–4.0 mm, compared to a range of 1.1–9.1 mm with S‐TPS‐RPM of bladder alone and 0.9–9.4 mm for simultaneous nonweighted registration. All registration methods resulted in good geometric accuracy on the bladder; average error values were all below 1.2 mm. Conclusions: : The weighted S‐TPS‐RPM registration algorithm with additional weight parameter allowed indirect control over structure‐specific flexibility in multistructure registrations of bladder and bladder tumor, enabling anatomically coherent registrations. The availability of an anatomically validated deformable registration method opens up the horizon for improvements in IGART for bladder cancer.